Antiepileptic Drug Adverse Cutaneous Reaction in Childhood - Yimenicioğlu, Sevgi; Ekici, Arzu; Türkeli, Ahmet; Bildirici, Yasar (Journal of Pediatric Epilepsy, 2022)
Antiepileptic drug (AED) side effects can result in treatment failure, morbidity, and mortality. Adverse cutaneous drug reactions (ACRs) frequently occur within the first 2 to 3 months of drug use. We wanted to discuss antiepileptic ACRs in childhood in this study. This was a study of 37 pediatric patients who were diagnosed with ACR and treated with AED in the last 5 years. Over a 5-year period, 37 (1.8%) of the 2,064 epilepsy patients had ACRs. There were 23 (62%) male patients and 14 (38%) female patients. Patients had a median age of 6 years (interquartile range: [IQR]: 3.5–10). The ACRs occurred in a median of 20 (IQR: 14–30) days. There were 28 (75%) patients receiving monotherapy and 9 (25%) patients receiving polytherapy. Overall, 22 (59.5%) of the 37 patients used aromatic drugs (AD), while 15 (40.5%) used nonaromatic drugs (NAD). Morbilliform eruptions accounted for the majority of ACRs (84%). Valproic acid (54%) was the most frequently used AED that resulted in ACRs. There was no significant difference in terms of eruption time, gender, or age between AD and NAD. Within 1 to 2 months of initiating a new AED, patients should be closely monitored for ACRs. If an ACR develops for one AED, greater caution should be taken when initiating the other AED. Although it is well established that ADs cause more skin reactions, we found that one of the NADs, valproic acid, causes more skin reactions.
Keywords: adverse cutaneous reaction; antiepileptic drug; aromatic drug; nonaromatic drug